Cell adhesion protein fibulin‐7 and its C‐terminal fragment negatively regulate monocyte and macrophage migration and functions in vitro and in vivo. Issue 9 (10th April 2018) - Sarangi, Pranita P.; Chakraborty, Papiya; Dash, Shiba Prasad; Ikeuchi, Tomoko; de Vega, Susana; Ambatipudi, Kiran; Wahl, Larry; Yamada, Yoshihiko
ABSTRACT: Fibulin‐7 (Fbln7) has been identified as the latest member of the fibulin family of secreted glycoproteins in developing teeth, functioning as a cell adhesion molecule and interacting with other matrix proteins, receptors, and growth factors. More recently, we have shown that the C‐terminal Fbln7 fragment (Fbln7‐C) has antiangiogenic activity in vitro. Fbln7 is also expressed in immune‐privileged tissues, such as eye and placenta, but its functional significance is unknown. In the current study, we show that human monocytes adhere to both full‐length Fbln7 (Fbln7‐FL) and Fbln7‐C, in part, via integrins α5 β1 and α2 β1 . Morphologic studies and surface expression analyses of CD14, mannose receptor (CD206), major histocompatibility complex II, and CD11b receptors revealed that both Fbln7‐FL and Fbln7‐C inhibit M‐CSF‐induced monocyte differentiation. Fbln7‐C had significantly greater negative effects on cell spreading and stress fiber formation, including the production of IL‐6 and metalloproteinase‐1/‐9 compared with Fbln7‐FL. Furthermore, in an LPS‐induced systemic inflammation model, Fbln7‐C and Fbln7‐FL reduced the infiltration of immune cells, such as neutrophils and macrophages, to the inflamed peritoneum. Thus, these results suggest that Fbln7 and Fbln7‐C could modulate the activity of immune cells and have therapeutic potential for inflammatory diseases.—Sarangi, P. P., Chakraborty, P., Dash, S. P., Ikeuchi, T., de Vega, S., Ambatipudi, K., Wahl, L., Yamada, Y. Cell adhesion protein fibulin‐7 and its C‐terminal fragment negatively regulate monocyte and macrophage migration and functions in vitro and in vivo . FASEB J. 32, 4889–4898 (2018). www.fasebj.org